Varying levels of concentrates in the rations of Sudan Desert sheep - El-Hag, G.A.; Mukhtar, A.M.S. (1978)
Seventy Sudan desert rams about one year old were purchased from Omdurman livestock market during September 1976 and taken to Khartoum university farm where they were ear tagged, weighed and divided into four groups of 16 animals each. The rations fed for the four group of animals were: Ration I: Hummra alone (control), Ration II: 75% Hummra + 25% concentrate, Ration III: 50% Hummra + 50%concentrate, Ration IV: 25% Hummra + 75% concentrates. Food supplied and food refusals were measured daily. Initial and final weights were taken from the average of three consecutive weighings. The experimental continued for 70 days. At the end of the feeding trail, 8 animals from each group were slaughtered after being weighed (slaughter weight). Besides the feeding trails, separate examinations were made for digestibility and nitrogen retention of the rations tested. The data on the daily gain showed clearly that animals on the test rations compared with those on the control ration gained substantially more and the difference between the two groups in the respect was greater in rations containing concentrates then the one consisting of roughage alone, but the difference in intakes was not statistically significant (P